Service-oriented sensor-actuator networks. - Rezgui, Abdelmounaam (IEEE Communications magazine)
Most approaches developed to query sensor-actuator networks (SANETs) are either application-specific or generic. Application-specific SANETs provide limited reusability, are not cost effective, and may require extensive reprogramming efforts to make the network able to serve new applications. Generic SANETs usually require that a sizeable code be deployed on the nodes regardless of the specific requirements of the application at hand. More important, they may not be optimized to fully exploit the specific characteristics and query patterns of a given application. In this article we introduce service-oriented SANETs (SOSANETs) as a novel approach to building customizable SANETs. SOSANETs provide the benefits of both application-specific SANETs (e.g., energy efficiency, scalability) and generic SANETs (e.g., reusability) and avoid most of their limitations. We implemented our approach in TinySOA, a SOSANET developed on top of TinyOS. We conducted an evaluation of TinySOA that included a comparison with TinyDB, an established query processing system for sensor networks. The obtained empirical results show that TinySOA outperforms TinyDB in many aspects including energy consumption, scalability, and response time.